(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article highlights the role of national ideas and spirituality in ensuring the stability of interethnic relations in Uzbekistan. It also discusses current issues in the field of national ideology and national identity in the context of global changes, in particular the protection of the spirituality of our people from growing ideological and spiritual threats in some regions of the world, especially in the hearts and minds of the younger generation.